The age‐old question: Thematic analysis of focus groups on physician experiences of aging in emergency medicine - William Binder; Casey O. Abrahams; Jordan M. Fox; Elizabeth Nestor; Janette Baird (Journal of the American College of Emergency Physicians Open)
Abstract Objectives Emergency medicine has a demanding work environment. Characteristics influencing longevity among older physicians in emergency medicine have been the subject of ongoing discussion. The American College of Emergency Physicians (ACEP) released a policy statement in 2009 suggesting accommodating emergency physicians in preretirement years. We engaged emergency physicians to determine awareness of the ACEP policy and issues faced in preretirement years. Methods We conducted a series of online focus group discussions with a purposive sample of emergency physicians, age ≥ 50 years. The discussion guide was developed from the ACEP policy statement and relevant literature. Groups were audio recorded, transcribed, and analyzed with a thematic coding system developed iteratively by the 4‐person team. Emerging themes were identified, organized, and presented with illustrative quotations. Results A total of 28 emergency physicians participated in 4 focus groups, with between 6 and 9 participants in each group. These physicians had between 17 and 35 years of clinical experience (median = 27), 6 were female (21%), and the majority (n = 26, 93%) worked in academic emergency medicine. Only 1 emergency physician was fully aware of the ACEP policy. Three principal content areas were identified: workload demands that change as physicians age, wellness and physician social equity, and senior emergency physician value. Interwoven across all of these was the focus on leadership and solutions to issues. Issues facing emergency physicians in their preretirement years were identified; commitment from emergency medicine site and national leadership and buy‐in from junior colleagues was emphasized. Generational conflicts in recognizing the contribution and needs of preretirement emergency physicians was a major barrier to solutions. Conclusions Workload demands, wellness and physician social equity, and concerns about value as a senior physician are major themes confronting preretirement emergency physicians. Generational divides, deficits in local and national leadership, and the health detriments of rotating schedules and night shifts are barriers to longevity in emergency medicine. Further research on the value of senior physicians and the impact of hospital and departmental financial models on adopting accommodations for senior emergency physicians is needed.